2021
DOI: 10.3390/cancers13112540
|View full text |Cite
|
Sign up to set email alerts
|

5-ALA Fluorescence Is a Powerful Prognostic Marker during Surgery of Low-Grade Gliomas (WHO Grade II)—Experience at Two Specialized Centers

Abstract: The prediction of the individual prognosis of low-grade glioma (LGG) patients is limited in routine clinical practice. Nowadays, 5-aminolevulinic acid (5-ALA) fluorescence is primarily applied for improved intraoperative visualization of high-grade gliomas. However, visible fluorescence is also observed in rare cases despite LGG histopathology and might be an indicator for aggressive tumor behavior. The aim of this study was thus to investigate the value of intraoperative 5-ALA fluorescence for prognosis in LG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…First, the visualization of tumor tissue and its discernment from healthy tissue is of utmost importance during neurooncological procedures. The introduction of 5-ALA-induced fluorescence has been a major scientific achievement in the intraoperative visualization of malignant tissue, which is independent of brain shift [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. In conventional microscopic surgery, tumor tissue “glows” after preoperatively administered 5-ALA and intraoperative switching from conventional white light to a blue light source, which is integrated into the microscope.…”
Section: Discussionmentioning
confidence: 99%
“…First, the visualization of tumor tissue and its discernment from healthy tissue is of utmost importance during neurooncological procedures. The introduction of 5-ALA-induced fluorescence has been a major scientific achievement in the intraoperative visualization of malignant tissue, which is independent of brain shift [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. In conventional microscopic surgery, tumor tissue “glows” after preoperatively administered 5-ALA and intraoperative switching from conventional white light to a blue light source, which is integrated into the microscope.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, according to the Results section, including Table 2 of the original publication of Jaber et al [5], only 16 IDH wildtype gliomas were indicated. Nevertheless, a higher portion of IDH wildtype gliomas were analyzed in the study by Jaber et al [5] compared to our study [6]. Due to the low number of IDH wildtype gliomas in our cohort (n = 5), the statistical power of a multivariate survival analysis was thus too low.…”
mentioning
confidence: 54%
“…We also thank the authors for the effort of summarizing and comparing the results of both studies [5,6]. Indeed, the number of isocitrate dehydrogenase (IDH) wildtype low-grade gliomas (LGG) was lower in our cohort (n = 5) compared to the study of Jaber et al [5].…”
mentioning
confidence: 77%
See 1 more Smart Citation
“… 21 Second, 5-ALA–induced fluorescence has proven to correlate with oncological prognosis in histologically verified low-grade gliomas. 5 , 22 Further confirmatory studies will need to show if these observations justify the expanding of FDA approval.…”
Section: Discussionmentioning
confidence: 99%